GENE-25. GWAS BY MOLECULAR SUBTYPE IDENTIFIED NOVEL RISK LOCI FOR ADULT DIFFUSE GLIOMA. (11th November 2019) - Eckel-Passow, Jeanette; Decker, Paul; Kosel, Matthew; Kollmeyer, Thomas; Molinaro, Annette; Rice, Terri; Drucker, Kristen; Hansen, Helen; McCoy, Lucie; Bracci, Paige; Wiemels, Joseph; Wiencke, John; et al.
Abstract: Genome-wide association studies (GWAS) have revealed that 25 regions in 24 genes are associated with adult diffuse glioma development. These regions were identified by performing GWAS of glioma overall and GWAS by pathology (GBM and nonGBM). Subsequently, these regions have been evaluated for associations with specific molecular subtypes. The 2016 WHO Classification of Tumors of the Central Nervous System utilizes two somatic alterations to molecularly-classify adult diffuse glioma: IDH mutation and 1p/19q codeletion. TERT promoter mutation has also been shown to be associated with age at diagnosis and patient outcome. We hypothesized that germline variants may increase susceptibility to, or interact with, these somatic alterations to accelerate the development of specific molecular subtypes of glioma. To test our hypothesis, we performed a GWAS by glioma molecular subtype – as defined by presence or absence of IDH and TERT somatic mutation and 1p/19q codeletion – utilizing a two-stage design and subsequent meta analysis that included 3001 total glioma cases and 2697 total controls. Data were imputed using the Michigan Server and logistic regression was used, adjusting for age and sex. The Cancer Genome Atlas (TCGA) data were used to perform an expression quantitative trait loci (eQTL) analysis on candidate germline variants. Variants in 2q37 and 7p22 were associated with IDH-mutated glioma (meta analysis p< 5x10-8). The eQTL analyses demonstrated significant associations between 2q37 variants and expression of nearby genes as well as associations between 7p22 variants and nearby genes (p< 0.0001). In conclusion, we identified and validated novel germline variants in two genes that are associated with etiology of IDH-mutated adult diffuse glioma.